Komunikasi Antarbudaya Terhadap Pelaksanaan Upacara Momboa Tumpe Dalam Proses Pengiriman Telur Burung Maleo - Falimu (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of writing this article is to present an overview of intercultural communication in the implementation of the tumpe ceremony through the process of sending maleo eggs to the Banggai Kingdom in Banggai Laut Regency through the momboa tumpe traditional ceremony. The method used is descriptive qualitative which includes observations, interviews and documentation. The implementation of the momboa tumpe ceremony in the process of sending maleo bird eggs in the Banggai kingdom, Banggai Laut Regency has meaningful requirements which include the delivery process, the value of indigenous peoples' responsibility, gratitude, togetherness and a culture of deliberation and Cultural Heritage through the Gathering between the Banggai Laut Community and the Batui District Community through the process of negotiating or exchanging symbolic systems in delivering maleo eggs to the king of Banggai through the momboa tumpe ritual.